THE IMPORTANCE OF HEDONIC AND SYMBOLIC VALUE ON CUSTOMER ENGAGEMENT AND ONLINE IMPULSIVE BUYING TENDENCY: THE CASE OF GENERATION Z - Amdar, Amdar; Wirakusuma, Alvin; Hertanto, Noel; Anggriani, Andi Nurhalizah; Adelfy, Muhammad Fadel; Ardyan, Elia (STIE Pelita Nusantara Semarang, 2024)
The phenomenon of impulsive online buying in Indonesia has become an important concern with the increasing use of the internet and e-commerce platforms, especially among Generation Z. Online impulsive buying is an unplanned purchasing action triggered by external stimuli, often driven by the hedonic and symbolic value of the product or service. This research aims to examine the influence of hedonic and symbolic values on customer engagement and the tendency for impulsive online buying, particularly among Generation Z. There were 216 respondents who filled out the online questionnaire. The respondents are individuals who have experience with online impulsive buying activity. The analysis used structural equation modeling partial least squares. The research findings indicate that hedonic and symbolic values have a positive and significant impact on customer engagement. Furthermore, customer engagement was found to have a positive and significant influence on online impulsive buying. The theoretical implications of this research emphasize the importance of a deep understanding of hedonic and symbolic motivations in the context of online consumer behavior. Managerially, these findings can be used by marketers to design more effective marketing strategies emphasizing the hedonic and symbolic values of their products, in order to enhance customer engagement and stimulate impulsive buying.